Herding behavior, information type, and overconfidence bias: an experimental study on novice investors’ investment decisions - Kresnawati, Etik; Sofia, Lina; Utami, Evy Rahman (Journal of Accounting and Investment, 2024)
Research aims: By the end of 2023, Indonesian Central Securities Depository data revealed a significant increase in the number of investors dominated by millennial investors (56.41%). They are categorized as novice investors who have distinctive characteristics from professional investors. This study, thus, aims to examine whether herding behavior dominates the characteristics of novice investors and whether information type and overconfidence bias affect the herding behavior of novice investors.Design/Methodology/Approach: This study used a quasi-experimental 2x2 mixed design on 42 student participants who were members of the Capital Market Study Group. The data obtained were then tested using non-parametric statistics.Research findings: The test results uncovered that herding dominated the investment behavior of novice investors. This behavior was supported by the information type that participants paid attention to in making decisions. However, testing for overconfidence demonstrated that this variable was not the cause of novice investors' herding behavior.Theoretical contribution/Originality: The results of this study contribute theoretically to the investment behavior of novice investors by strengthening the argument that they tend to behave herding when making stock investment decisions. Testing with an experimental design allows researchers to confirm that such herding behavior is reinforced by the preference for the information type they use in decision-making. The results also provide insight into the fact that the overconfidence level of novice investors may be different from that of professional investors.Practitioner/Policy implication: The tendency of herding behavior of novice investors needs attention from the Financial Services Authority as a regulator to consider protection for novice investors who dominate the number of investors in the capital market.Research limitation/Implication: The tests in this study employed non-parametric statistics, which are not as good as parametric tests, so the study results should be understood wisely. Future research needs to consider the adequacy of the sample and use capital market groups in several universities to improve sample quality.